Pengaruh formulasi minuman herbal daun beluntas dan kelopak bunga rosella terhadap kualitas, aktivitas antioksidan, dan sifat sensori - Paini Sri Widyawati; Tarsisius Dwi Wibawa Budianta; Thomas Indarto Putut Suseno; Jennifer Yauwnita; Rahagel Otto Hadina (AGROINTEK, 2025)
Pluchea indica Less has been processed to be an herbal drink because it contains many bioactive compounds that have the potential as an antioxidant source. Pluchea herbal drink has low antioxidant activity, sensory acceptance, and unattractive color, so other herbal sources are required to improve antioxidant activity, color, and panelist preference for the drink. One of them is rosella flower petals. This research was conducted to study the effect of the formulation of pluchea leaves-rosella flower petals herbal drink on the quality, antioxidant activity, and sensory properties of herbal drinks. The proportion increasing of rosella flower petals had a significant effect on increasing water content, activity water (Aw), and redness (a*) as well as the decreasing of lightness (L*), yellowness (b*), chroma (C) and hue (oh) of herbal drink powder. The increase of total acid, turbidity, and redness (a*) also was as well as the decrease of pH, lightness (L*), yellowness (b*), chroma (C), and hue (oh) of steeping water of herbal drink. However, the bioactive contents, including total phenolic content (TPC), total flavonoid content (TFC), and total tannin content (TTC), and the antioxidant activities, including DPPH free radical scavenging activity (DPPH) and ferric reducing antioxidant power (FRAP), was decreased significantly. Meanwhile, panelists' hedonic acceptance decreased the taste and increased the color and aroma of the steeping water of the herbal drink. Proportion 40:60 (%w/w) was the best treatment with a total score of 0.83, which improved physicochemical and sensory quality, with pH 3.19±0.12, total acid 2.06±0.08%, turbidity 643.00±9.35 NTU, lightness 3.05±0.17, redness 2.63±0.19, yellowness 1.65±0.06, chroma 3.10±0.18, hue 34.43±0.26, TPC 0.062±0.004 (mg GAE/g sample dry base), TFC 0.027±0.004 (mg CE/g sample dry base), TTC 0.066±0.004 (mg TAE/g sample dry base), DPPH 0.025± 0.006 (mg GAE/g sample dry base), FRAP 0.016±0.003 (mg GAE/g sample dry base), preference for color 5.69±1.05, taste 4.48±1.06, and aroma 5.74±1.02.